2016
DOI: 10.1021/acs.iecr.6b03045
|View full text |Cite
|
Sign up to set email alerts
|

Process Knowledge Discovery Using Sparse Principal Component Analysis

Abstract: As the goals of ensuring process safety and energy efficiency become ever more challenging, engineers increasingly rely on data collected from such processes for informed decision making. During recent decades, extracting and interpreting valuable process information from large historical data sets have been an active area of research. Among the methods used, principal component analysis (PCA) is a well-established technique that allows for dimensionality reduction for large data sets by finding new uncorrelat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Research in this area is particularly dependent on the abundance of faulty process data to allow for proper training of the data analytics models to identify the right fault and the corresponding root cause, which can once again be greatly facilitated using the proposed GUI. Sparse chemometrics methods have been proposed 30–32 to enable the identification of the root cause but as in detection we expect more research to be performed using machine learning methods 22,33,34 . For the learning algorithms, the crucial issue will be the availability of abundant and realistic data to train and test these algorithms.…”
Section: Application Of Gui Outputmentioning
confidence: 99%
“…Research in this area is particularly dependent on the abundance of faulty process data to allow for proper training of the data analytics models to identify the right fault and the corresponding root cause, which can once again be greatly facilitated using the proposed GUI. Sparse chemometrics methods have been proposed 30–32 to enable the identification of the root cause but as in detection we expect more research to be performed using machine learning methods 22,33,34 . For the learning algorithms, the crucial issue will be the availability of abundant and realistic data to train and test these algorithms.…”
Section: Application Of Gui Outputmentioning
confidence: 99%
“…As opposed to early process measurements that were limited to key variables sampled at a few strategic locations, in modern processes, numerous process states and physical properties can be accessed and stored with high sampling frequencies with the aid of a vast network of sensor arrays. 3 A key step to analyzing such large data sets is effective complexity reduction, during which the data size is reduced and the fundamental information structure is preserved. Principal component analysis (PCA) is a popular method for achieving dimension reduction with applications in various scientific fields, 4 especially in the field of statistical process monitoring.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In a related but rather different study, Gao et al 3 developed a high-level SPCA algorithm based on SPCA to obtain loading vectors with high captured variance and called it the forward SPCA. The approach was then applied to the Tennessee Eastman process to discover underlying correlations.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ability to diagnose a fault is greatly enhanced by improving the interpretability to the components with most contributions to the fault. To this end, Gajjar et al 21 showed that, as compared to PCA, SPCA accurately identified the faulty variables and aided the process of fault diagnosis.…”
Section: ■ Introductionmentioning
confidence: 99%